Evaluation of three dimensional construct engineered from poly(Lactic-co-glycolic acid)/fibrin hybrid scaffold using rabbit bone marrow mesenchymal stem cells for osteochondral defect repair - Abdul Rahman, Rozlin; Mohamad Sukri, Norhamiza; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa'zamuddin; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin; Abdul Rahman, Suzanah; Sha'ban, Munirah (Universiti Teknologi Malaysia, 2015)
Articular cartilage has poor repair capacity due to its avascular and aneural properties and has relatively few cells. This study investigated the ability of autologous implantation approach using three dimensional (3D) constructs engineered from bone marrow mesenchymal stem cells (BMSCs) seeded on poly(lactic-co-glycolic acid) (PLGA) with or without fibrin as cells carrier for the repair of osteochondral defect in rabbit model. The engineered 3D constructs – PLGA/Fibrin/BMSCs and PLGA/BMSCs – were cultured for 3 weeks in vitro and implanted autologously to the osteochondral defect created in the rabbit knee. The in vivo constructs were harvested and evaluated by means of gross observation, histology assessment, gene expression study, sulphated glycosaminoglycan (sGAG) production assay and biomechanical evaluation at 6 and 12 weeks post implantation. The results showed that the osteochondral defects treated with the PLGA/Fibrin/BMSCs constructs exhibited better repairment, more cartilaginous extracellular matrix, higher sGAG production, superior compressive strength and more intense expression of chondrogenic marker genes than the PLGA/BMSCs group. This study suggested that the PLGA/Fibrin/BMSCs has the potential to treat osteochondral defect and may be presented as a viable therapeutic option for those who would be in need from the life-extending benefits of tissue replacement or repair.